HARMFUL CONDITIONS ON THE DENTAL STATUS OF POULTRY FARM WORKERS - T. Pupin; O. Kardashevska (Український стоматологічний альманах)
The results of dental examination of 120 poultry farm workers of Zboryv city are displayed in the article. Examination determined the dental status of the patients, decay intensity of hard tissues of teeth, oral hygiene level, prevalence rate of non-carious diseases of teeth and inflammatory periodontal diseases level, condition of the oral mucosa depending on the length of work on the poultry farm. Prevalence of dentition and periodontal tissues diseases in poultry farm employees has been identified, it requires special attention of working conditions and its health effect. Improvement of dental care for poultry farm staff who meets some groups of harmful factors becomes so important in this regard.